PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA E-KOMIK KERAGAMAN BUDAYA TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IV SD - Nabila Chusnul Khotimah; Arif Mahya Fanny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by E-Comic media on the problem-solving abilities of fourth-grade students on cultural diversity material. The study used a quantitative approach with a quasi-experimental design of one group pretest-posttest type. The research subjects were 25 students of SDN Dukuh Kupang II Surabaya. The instrument was a descriptive test of problem-solving abilities that had been validated by experts. The average pretest score of 51.80 increased to 76.00 in the posttest. The results of the paired sample t-test showed a t value = -6.136 with a significance of 0.000 (<0.05) so that there was a significant increase. The results showed that the integration of PBL and E-Comic media was able to increase engagement, critical thinking, and the ability to solve problems systematically.